2019
DOI: 10.1177/1476718x19885993
|View full text |Cite
|
Sign up to set email alerts
|

Pre-K teachers’ perspectives on factors that influence their experiences through universal Pre-K policy changes in New York City

Abstract: The focus of this study is preschool teachers’ perspectives on their experiences during a Pre-K expansion in New York City. The expansion brought on neoliberal approaches to curriculum, child assessment, quality improvement, and instructional support in classrooms, and these changes in turn heightened expectations for accountability. This has required new sets of skills and resources for early childhood educators to implement the policy as enactors. Using an implementation research framework and a multiple cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Because student teachers have not had time to form certain teaching patterns in the beginning stage of becoming teachers, if these unfounded beliefs are changed, their future teaching practice and students' learning can be positively affected (Zheng, 2009 ; Voss and Kunter, 2019 ). For instance, Akaba et al ( 2020 ) examined pre-service teachers' beliefs concerning school policy adjustments, pinpointing that “individualized, localized support” and “coherent communication” (p. 13) between policy makers and pre-service teachers can largely affect pre-service teachers' teaching experiences as well as improving their teaching quality. Their findings showed that pre-service teachers long for more pedagogical autonomy during the policy decision-making process and teaching practice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Because student teachers have not had time to form certain teaching patterns in the beginning stage of becoming teachers, if these unfounded beliefs are changed, their future teaching practice and students' learning can be positively affected (Zheng, 2009 ; Voss and Kunter, 2019 ). For instance, Akaba et al ( 2020 ) examined pre-service teachers' beliefs concerning school policy adjustments, pinpointing that “individualized, localized support” and “coherent communication” (p. 13) between policy makers and pre-service teachers can largely affect pre-service teachers' teaching experiences as well as improving their teaching quality. Their findings showed that pre-service teachers long for more pedagogical autonomy during the policy decision-making process and teaching practice.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Teacher beliefs have been shown to be influenced by a teacher’s personal experience [ 15 , 16 ], teaching experience [ 16 ], educational background [ 17 ], and colleague support [ 16 ]. Moreover, the literature has provided insights into teacher beliefs concerning teaching practice [ 18 , 19 , 20 ], teacher education [ 21 , 22 , 23 , 24 ], learning experience [ 25 ], curriculum design [ 14 , 26 ] parent involvement [ 27 ], learner autonomy [ 13 ], and corrective feedback [ 28 , 29 ]. Researchers have also suggested that there is a strong relationship between teacher beliefs and their teaching practice in EFL classrooms [ 1 , 13 , 30 , 31 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Wilinski ( 2017 ), however, describes the unequal variability of access to opportunities for PD experiences based on school settings (public district school or community-based childcare center) due to inflexibility caused by program scheduling and low adult coverage, as a result of Wisconsin’s statewide universal Pre-K program policy. While teachers who are not provided PD opportunities fail to learn about policy reform and recommended practices that are directly related to accountability, they are also excluded from their professional communities that might help them develop stronger relationships with their peers and colleagues (Akaba et al, 2020a ). Therefore, Pre-K teachers and administrators at CBOs experience the need to consistently adapt their identities and expectations to navigate the public Pre-K system so that they meet the requirements of the Pre-K policy.…”
Section: Literature Reviewmentioning
confidence: 99%